PROTECTIVE EFFECTS OF BOERHAVIA DIFFUSA LINN. (NICTAGINACEAE) ON LIVER OF STREPTOZOTOCIN-INDUCED DIABETIC RATS - LAGNIKA, LATIFOU (My University, 2019)
The aim of this study was to evaluate the hepatoprotective of Boerhavia diffusa Linn. used in Benin and other countries to manage control and treat diabetes. Streptozotocin (STZ) is selectively toxic to cells in the pancreatic islets. It is well known that STZ causes specific death of B cells and induces diabetes mellitus. Rats were kept under eighteen hours fasting and then subjected to diabetic by intraperitoneal (i.p.) injection of streptozotocin (40 mg/kg body weight). The duration of experiment was 28 days. Blood glucose levels, the relative percentage of liver weight and liver histology were studied. There were significant increase in relative liver weight, blood glucose levels in diabetic untreated comparing to normoglycemic (control) (p<0.05). The results showed several morphological and histological alterations in liver tissues. These pathological changes were ameliorated in the Boerhavia diffusa Linn. extract and glibenclamide treated rats. Boerhavia diffusa Linn. extract has a protective effect on tissue damage probably due to its antioxidant activity and possess the ability to regenerate β-cell in STZ-induced diabetic rats.
Keywords: Boerhavia Diffusa Linn. (Nyctaginaceae); Diabetes Mellitus; Glibenclamide; Liver; Rats; Streptozotocin.